Utilization of the Song Terus Museum as a Learning Resource in Indonesia - Kusumaningsih, Reni; Miftahuddin, Miftahuddin; Wiratmoko, Dheny (Harmoni Sosial: Jurnal Pendidikan IPS, 2024)
This study aims to describe using the Song Terus Museum as a learning resource for history education students of STKIP PGRI Pacitan. This study is described using qualitative methods. The research location is at the Song Terus Pacitan Museum and STKIP PGRI Pacitan. The study subjects were lecturers of History Education, students of the History Education study program, and the person in charge of the Song Terus Pacitan Museum. Data sources come from primary data sources and secondary data sources. Data collection techniques and instruments used are observation, interviews, and documentation. In this study, researchers used modern data analysis techniques Miles and Huberman. The results of this study show that almost all collections of the Song Terus Museum can be used as learning resources. After all, the collections include cultural products from prehistoric to modern. In general, the use of the Song Terus Museum as a learning resource by conducting visits to make observations according to the tasks given, the effectiveness of learning before and after the use of the Song Terus Museum as a learning resource can be seen from the differences in the level of understanding, interest, and motivation of students towards history subject matter, and the obstacles faced by lecturers and students in utilizing the Song Terus Museum as a source of learning history is the place, because the distance between the campus and the museum is quite far.